Preclinical Evaluation of Human Pluripotent Stem Cells-Derived Pancreatic Progenitor Cells (hPSCs-PPs) Using Transgenic Zebrafish Models - Zahra Morshed (15430067) (2023)
Poster by Zahra Morshed (Royan Institute for Reproductive Biomedicine), Mohamad Rezaie (Royan Institute for Reproductive Biomedicine), Behrouz Asgari Abibeiglou (Royan Institute for Stem Cell Biology and Technology) , Zahra Ghezelatagh (Royan Institute for Reproductive Biomedicine) , and Yaser Tahamtani  (Royan Institute for Reproductive Biomedicine, Royan Institute for Stem Cell Biology and Technology) Background: Human pluripotent stem cells (hPSC) derived pancreatic cells (PCs) has been recently introduced as a promising cell source for cell replacement therapy for type I diabetic patients. Before conducting clinical trials, laboratory made pancreatic cells need to be characterized through preclinical evaluations. Mice, rats and higher non-human primates have been common models for evaluating toxicity, feasibility and efficacy of this lab-made cells. Despite having many similarities to humans, these models have limitations However, since the technology of differentiating hPSC into different PCs is still under development, introducing new methods that enable us to faster and cheaper compare our generated cells in-vivo is necessary. Zebrafish have been introduced as a proper animal model for evaluating functionality of human cells due to its fast breeding, transparent larvae, and lack of acquired immune system in the first 14 days of its life. High-throughput zebrafish cell injection platform is also available for screening different cell types. Objective:  The aim is to examine zebrafish as a model for hPSCs-PPs injection and to evaluate their viability, integration into the pancreatic niche, further differentiation and functionality. Methods: Using our previously published differentiation protocol, hPSCs were differentiated into PDX1+/NKX6.1+ PPs within 14 days in 37°C. Afterward, the cells marked with the vital dye pkh26 (red). The transgenic zebrafish model Tg (ins: Kaede-NTR) larvae (kept at 28°C water) were used, which have a green fluorescent pancreas that can be abolished by metronidazole (MTZ). For cell injection, the 3-day-old larvae anesthetized with Tricain, then transferred to the PDMS mold plate, and microinjected under the fluorescent microscope. To check the viability of zebrafish after injection, images taken every day using an optical microscope. Also, to determine the viability of the injected cells, every second day from day 3 to 14, the pancreatic portion of the larvae, were detected by confocal microscopy. Results: As the first step of this project, to optimize the injection site, obtain the correct number of cells for injection, and evaluate the survival rate of larvae and cells after injection, hESCs were injected into the pancreatic niche of Tg (ins: Kaede-NTR) zebrafish. Results showed that the best injection site was pancreatic niche which is labeled by kaede, and the optimum number of cells injected was a volume of 1 µl containing 50-250 cells. larvae viability of 80% ± 20% was observed after injection which was probably due to larvae maintenance at 32°C. Larvae remained viable until 14 days and red hESCs were traceable up to 7 days after injection in tissues near and also far from the injection site which is representative of cell migration after transplantation. In the next step, we intend to evaluate the survival, differentiation, and function of hESCs-PPs in our zebrafish model by injecting hESCs-PPs into zebrafish larvae with/without distraction of their endogenous pancreatic beta cells. Conclusion: This method can be used to follow further differentiation and functionality of hPSCs-PPs in zebrafish larvae as a good assay for evaluating and comparing different differentiation protocols in vivo.